4(d+3) - 3(d-2) = 1.2=> 4d + 12 - 3d + 6 = 1.2=> d + 18 = 1.2=> d = 1.2 - 18therefore, d = - 16.8

1 year ago

Answered By Leila S

4d+13-3d=1.2

d+13=1.2

d=-13+1.2

d=-11.8

1 year ago

Answered By Mandy H

To solve for d get it all by itself on one side the equation sign...

Use the distributive property to multiply the number in front of the bracket (i.e. 4 and -3 (note the - sign makes 3 become -3 so remember integer rules*) with everything inside the bracket.

Then group like terms (i.e. 4d - 3d = 1d) to simplify the equation

d + 18 = 1.2

To get d by itself, subtract 18 on the left side of the equation. What you do on one side you have to do to the other so...

d + 18 - 18 = 1.2 - 18

d = -16.8

*integer rules: (-#) * (-#) = +#

1 year ago

Answered By Leila S

Revised answer:

4d+12-3d+6=1.2

4d-3d+12+6=1.2

d+18=1.2

d=-18+1.2

d=-16.8

1 year ago

Answered By Sosimo H

4(d+3)-3(d-2)=1.2

4d+12-3d+6=1.2

4d-3d=1.2-12-6

d=1.2-18=-16.8

d=-16.8

1 year ago

Answered By Ruth F

4(d+3) - 3(d-2)=1.2

The first thing you need to do is to get rid of the brackets. In order to do that you need to mutiply what is outside of the bracket with each of the terms inside of the brackets.

4(d+3) + (-3)(d-2) = 1.2

4xd + 4x3 + (-3)xd + (-3)x(-2) = 1.2

4d + 12 + (-3d) + 6 = 1.2

Now group the "like terms" which are the variables with variables and numbers with numbers

4d + (-3d) + 12 + 6 = 1.2

1d +18 = 1.2

Now you need to get the 1d (which can also just be called "d" because the coefficient is 1) on one side of the equation and the numbers on the other side of the equation. You need to do the same thing to each side in order to keep the equation balanced and equal.

1 year ago

## Answered By Hamza S

4d+7-3d+6 = 1.2

4d-3d-7+6 =1.2

d - 1 = 1.2

d = 1.2 + 1

d = 2.2

1 year ago

## Answered By Hamza S

SOrry this the right solution for find D

4d + 12 -3d + 6 = 1.2

d + 18 = 1.2

d = 1.2 - 18

d = -16.8

1 year ago

## Answered By Mohammad Sadav Imtiaz A

4(d+3) - 3(d-2) = 1.2=> 4d + 12 - 3d + 6 = 1.2=> d + 18 = 1.2=> d = 1.2 - 18therefore, d = - 16.8

1 year ago

## Answered By Leila S

4d+13-3d=1.2

d+13=1.2

d=-13+1.2

d=-11.8

1 year ago

## Answered By Mandy H

To solve for d get it all by itself on one side the equation sign...

Use the distributive property to multiply the number in front of the bracket (i.e. 4 and -3 (note the - sign makes 3 become -3 so remember integer rules*) with everything inside the bracket.

4(d+3) - 3(d-2) = 1.2 becomes 4d + 12 - 3d + 6 = 1.2

Then group like terms (i.e. 4d - 3d = 1d) to simplify the equation

d + 18 = 1.2

To get d by itself, subtract 18 on the left side of the equation. What you do on one side you have to do to the other so...

d + 18 - 18 = 1.2 - 18

d = -16.8

*integer rules: (-#) * (-#) = +#

1 year ago

## Answered By Leila S

Revised answer:

4d+12-3d+6=1.2

4d-3d+12+6=1.2

d+18=1.2

d=-18+1.2

d=-16.8

1 year ago

## Answered By Sosimo H

4(d+3)-3(d-2)=1.2

4d+12-3d+6=1.2

4d-3d=1.2-12-6

d=1.2-18=-16.8

d=-16.8

1 year ago

## Answered By Ruth F

4(d+3) - 3(d-2)=1.2

The first thing you need to do is to get rid of the brackets. In order to do that you need to mutiply what is outside of the bracket with each of the terms inside of the brackets.

4(d+3) + (-3)(d-2) = 1.2

4xd + 4x3 + (-3)xd + (-3)x(-2) = 1.2

4d + 12 + (-3d) + 6 = 1.2

Now group the "like terms" which are the variables with variables and numbers with numbers

4d + (-3d) + 12 + 6 = 1.2

1d +18 = 1.2

Now you need to get the 1d (which can also just be called "d" because the coefficient is 1) on one side of the equation and the numbers on the other side of the equation. You need to do the same thing to each side in order to keep the equation balanced and equal.

d + 18 - 18 = 1.2 - 18

d + 0 = -16.8

d = -16.8